Mycobacterium chimaera Outbreak Associated With Heater-Cooler Devices: Piecing the Puzzle Together. (14th November 2016) - Sommerstein, Rami; Schreiber, Peter W.; Diekema, Daniel J.; Edmond, Michael B.; Hasse, Barbara; Marschall, Jonas; Sax, Hugo
Abstract : An outbreak of invasive Mycobacterium chimaera infections associated with heater-cooler devices (HCDs) has now affected patients in several countries on different continents. Clinical infections are characterized by delayed diagnosis, inadequate treatment response to antimicrobial agents, and poor prognosis. Outbreak investigators found M. chimaera in HCD water circuits and air samples while HCDs were running, suggesting that transmission from the HCD to the surgical site occurs via the airborne route. New HCDs at the manufacturing site were also contaminated with M. chimaera, and recent whole-genome sequencing data suggest a point source. Some guidance on screening for M. chimaera colonization in HCD water and exhaust air is available. In contrast, reliable disinfection procedures are not well described, and it is not yet known whether eradication of M. chimaera from a contaminated HCD can be achieved. Meanwhile, strict separation of the HCD from operating room air is necessary to ensure patient safety, and these efforts may require engineering solutions. While our understanding of the causes and the extent of the M. chimaera outbreak is growing, several aspects of patient management, device handling, and risk mitigation still require clarification. Infect Control Hosp Epidemiol 2016;1–6